ASSOCIATIONS OF VERY LOW-DENSITY LIPOPROTEIN RECEPTOR (VLDLR) GENE POLYMORPHISMS WITH EGG PRODUCTION TRAITS IN IRAQI LOCAL BROWN CHICKENS - & et al., Abdulwahid (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
Very low-density lipoprotein receptor gene (VLDLR) is a part of the low-density lipoprotein receptor (LDLR) family. VLDLR plays important roles in transport egg yolk precursor to the oocyte. This work was conducted to study the effect of VLDLR polymorphism on the productive performance of local Iraqi chickens. In this study, the VLDLR gene was studied using blood samples of 173 pedigreed hens aged 47 weeks representing the third generation selected for high egg production. Genotypic and alleles frequencies in addition to the association between genotypes and egg production, egg weight and egg mass from onset eggs laid to the 80 weeks of age were investigated. The results showed that the genotypic and allelic frequencies of the VLDLR in 173 chickens did not agree with Hardy-Weinberg equilibrium (P<0.0307). The genotypic frequencies were 94.7 and 5.3% for both GG and GT genotypes respectively while, the allele frequency of genes G and T were 97.4 and 2.6%, respectively. The results showed an increase (P<0.0001) in egg production, egg weight and egg of GG genotypes compared to GT genotypes. This finding supports the previous results of VLDLR as a compromising gene. The current results approved that the VLDLR gene can be used as a candidate gene for modulating and improving egg production traits in Iraqi local chickens.